Motivasi dan inovasi kewirausahaan pengusaha: Studi kasus berwirausaha pada pengusaha di singaraja - Hasanah, Uswatun (Maliki Interdisciplinary Journal, 2024)
Entrepreneurship is an activity to improve people’s welfare in the sense of a better and quality standard of living. Entrepreneurship plays a very large role in economic development and growth. So this research is considered very important to carry out. The aim of this research is to find out about the description of motivation and innovation carried out by an entrepreneur in entrepreneurship. This research is also to determine the obstacles and challenges in entrepreneurship carried out by entrepreneurs in Singaraja. This research has a qualitative approach and uses the interview method. This research involved one main source in the Singaraja area. The results of this research are that the motivation for entrepreneurs to enter the world of entrepreneurship is the entrepreneurial spirit they already have and there are several incentives. From the soul. Of the business developments carried out by young entrepreneurs, the most prominent are initial capital strategies in entrepreneurship, strategic location selection for marketing their products, competitive strategies to survive market competition with several innovations. From obstacles or problems that arise in entrepreneurship carried out by entrepreneurs. There are several business obstacles faced, such as market competition and employee human resources.